Polystyrene biodegradation by Pseudomonas sp. strain PVGSPCDU isolated from Superworm gut - Veeravajhula, Pradeep; Raju, Nalvothula; Prasad Gurram, Shyam (Journal of Neonatal Surgery, 2025)
Massive amounts of plastic garbage are a serious social problem. There have been several initiatives to address the issue of plastic trash, including techniques for the natural decomposition of plastic. Since polystyrene (PS) is currently one of the plastics most often utilized in numerous industries, its degradation is a serious worldwide concern. In this study, we identified a Pseudomonas sp. Strain PVGSPCDU bacterium that breaks down PS from the superworms' guts. The breakdown of PS by Pseudomonas sp. has hardly been investigated up to this point. Using electronic microscopy, we investigated PS degradation and recorded atomic distribution and contact angle changes with water droplets on the PS surface, which indicate a chemical transition from hydrophobicity to hydrophilicity. Using Fourier transform-infrared spectroscopy (FT-IR), we investigated chemical structural changes during PS degradation by Pseudomonas sp. to look for the formation of C=O bonds and shifts towards hydrophilicity. According to our research, Pseudomonas, which is found in the superworms' guts, contributes to the breakdown of plastics after consumption. Therefore, the results of this study are important because they show a possible remedy for PS degradation in addition to revealing a new role for Pseudomonas in superworms' guts